The Survival of the Poetic Mode in Postmodern Filmic Language: Michael Almereyda’s Hamlet - Streitmann, Ágnes (FOCUS: Papers in English Literary and Cultural Studies, 2024)
In discussing Michael Almereyda’s Hamlet (2000) I am mostly concerned with the relationship between the Shakespearean text/language and the visual image as it manifests itself in the filmic language this adaptation uses. I intend to point out that unlike, for example, Kenneth Branagh’s screen versions of Shakespeare, which are characterized by an essentially realistic approach aimed at easing the translation of the Shakespearean text into the language of the cinema, Almereyda’s Hamlet, like the other postmodern filmic reinterpretations of the nineties, foreground the clash between the early modern text and postmodern mise-en-scène. By employing a kind of nonillusionistic, eclectic visual style these postmodern productions call our attention to the incongruities and defy conventional expectations of location, character, and narrative.